Improving the efficiency, safety and manageability of oil transportation processes - D. V. Shvechihin; M. A. Sheikina (Вестник университета)
The article is devoted to the analysis of the main opportunities for the digital transformation of an oil company, which are based on improving the efficiency, safety and controllability of production processes, obtaining additional economic benefits, and achieving leadership in terms of innovation. For the development and success of an oil and gas company, it is necessary to introduce measures to increase its economic growth, sustainability and competitiveness in the market. A key component of a business transformation strategy is digital transformation. The authors analysed the challenges for the digital transformation of the oil and gas industry: changing the importance of oil as an energy source, changing the market, business conditions, technology development, and environmental and social factors. The strategic directions for the development of digital transformation are considered and the main aspects of its roadmap are presented. The key success factors for the digital transformation of an oil company are identified.